Recuperação da palha da cana-de-açúcar para a produção de energia elétrica e etanol celulósico - Redígolo, Silvio César Rosa [UNESP] (2014)
With the growth of mechanized harvesting driven by environmental laws that restrict the burning of straw, there was an increase in the amount of straw left in the field. This situation have been studied by the sugarcane mill factories with respect to the technology employed in gathering and transportation of straw, as well as the utilization of this biomass, which can be mixed with the bagasse to increase cogeneration of electricity or to produce cellulosic ethanol. In the present study, the use of straw transported with the sugarcane to industry by trucks was considered although there is the possibility of packing it before transporting. Therefore different cases for straw utilization in an industrial plant that produces sugar, ethanol (anhydrous and hydrated) and electricity were thermodynamically analyzed, considering the increase of electricity production, by means incorporation of a boiler and a condensation turbogenerator in the cogeneration system, and, also, taking into account the production of cellulosic ethanol, by installing an annexed plant for this purpose. For each case studied an economic analysis to identify investments, the internal rate of return and net present value, in order to obtain feasibility conditions, was carried out. The final considerations presented situations of return on investment for cases where sale values above the currently practiced in the marketing of MWh in contract and negotiated price of anhydrous ethanol with fuel distributors were considered